Public governance in Denmark : meeting the global mega-challenges of the 21st century? - Krogh, Andreas Hagedorn; Agger, Annika; Triantafillou, Peter (Emerald Publishing Limited, 2022)
Societies all over the world are facing a host of daunting problems, including poverty, persistent unemployment, income inequality, unequal distribution of political power and participation, ageing populations, uncontrolled migration, and climate change. Public Governance in Denmark: Meeting the Global Mega-Challenges of the 21st Century? provides a nuanced account of how Denmark handles these urgent societal problems. Offering up-to-date academic analysis of Danish public governance, this edited volume encourages an informed and balanced debate about formulating and adopting political reform with reference to 'the Danish model'. The authors explore how recent public governance changes have turned the Danish welfare state into a mix of a neo-Weberian state and an enabling state, deploying its considerable resources to create economic growth for the benefit of most Danes, satisfying the needs of citizens and businesses, and developing collaborative solutions to complex problems. Still, not all Danish policy changes have been successful and evolving problems require further reforms in the years to come. Public Governance in Denmark will be of great interest to students and scholars within the fields of public administration, governance, policy and politics as well as policy professionals engaged in analyzing, designing, and evaluating public policies and governance strategies.